2008
DOI: 10.5507/bp.2008.034
|View full text |Cite
|
Sign up to set email alerts
|

Pictorial Cognitive Task Resolution and Dynamics of Event-Related Potentials

Abstract: Aims:To judge whether and how the character of the visual stimulus and type of cognitive task aff ects brain eventrelated potentials (ERPs).Methods: ERPs to three types of visual stimuli (white blank oval on a dark background, unfolded cube and net of sixteen small squares) were recorded from nine scalp sites and saved on a computer. Special software was used for off -line analysis of the ERPs.Results: The presentation of each of the three visual stimuli used was followed by ERPs consisting of two negative (N1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…This assumption is supported by our earlier findings 14,15 as well as by the dynamics of average FM pertinent to cognitive task solving described in the present paper; the average FM calculated for each of EEG records including P3 and P4 significantly decreased during the mental load related to solving each of two cognitive tasks.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This assumption is supported by our earlier findings 14,15 as well as by the dynamics of average FM pertinent to cognitive task solving described in the present paper; the average FM calculated for each of EEG records including P3 and P4 significantly decreased during the mental load related to solving each of two cognitive tasks.…”
Section: Discussionsupporting
confidence: 76%
“…The experimental paradigm, procedures, features of visual stimuli and method of data acquisition were described in detail in our recent paper 15 . Here only the principles of the data analysis are described.…”
Section: Methodsmentioning
confidence: 99%
“…Much of the literature on the relationships between cognitive demands and metabolic measures of work have been hampered by manipulations that produce rather small changes in performance. [47][48][49] In closing, we have shown that it is possible to characterize the relationships among cognitive demands, neural activity, and energy expended in the context of variations in iron status. Critically, we have shown that two distinct aspects of iron status-as indexed by sFt and Hb-play two distinct roles in these relationships.…”
Section: Discussionmentioning
confidence: 93%
“…The first and most obvious is that the finding of a positive relationship between metabolic energy expended and GFP needs to be replicated. Of concern here is the fact that we used large variations in workload-much larger than those used in earlier studies of the effect of cognitive workload on metabolic measures (Garde, Laursen, Jørgensen, & Jensen, 2002;Petrek, 2008Petrek, , 2009. It may be that the positive relationship that we obtained is only observable at high levels of demand.…”
Section: Discussionmentioning
confidence: 95%